2022
DOI: 10.1186/s12879-022-07192-x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary infection in COVID-19 critically ill patients: a retrospective single-center evaluation

Abstract: Background Patients infected with severe acute respiratory syndrome coronavirus (SARS-CoV-2) can develop severe illness necessitating intensive care admission. Critically ill patients are susceptible for the development of secondary bacterial infections. Due to a combination of virus- and drug-induced immunosuppression, critically ill patients with corona virus disease 2019 (COVID-19) may even have a higher risk of developing a secondary infection. These secondary infections can aggravate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 31 publications
8
62
1
3
Order By: Relevance
“…Interestingly, we also observed that COVID-19 severe patients might have an increased risk of bacterial, fungal infection compared to asymptomatic patients. This observation of reduced viral infection but increased secondary infection aligns with previous studies on COVID-19 patients [129, 130]. The immune response involved in viral and bacterial infection shares different immune components [131136].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we also observed that COVID-19 severe patients might have an increased risk of bacterial, fungal infection compared to asymptomatic patients. This observation of reduced viral infection but increased secondary infection aligns with previous studies on COVID-19 patients [129, 130]. The immune response involved in viral and bacterial infection shares different immune components [131136].…”
Section: Discussionsupporting
confidence: 90%
“…Beyond severity due to oxygen requirement during hospitalization, the appearance of secondary infections remains a major issue in the management of COVID-19 patients [ 3 , 4 , 8 , 31 ]. We compared the baseline parameters, classifying patients according to whether they developed secondary infections during their stay.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we have described a high-dimensional comprehensive study of the baseline clinical and immunological differences in COVID-19 patients during the first wave of the pandemic in Madrid, Spain. We have defined potential early markers (upon arrival at ED) associated with both hospital requirement and one of the biggest complications in these patients, secondary infections [ 3 , 4 , 8 ]. In addition, thanks to the collection of longitudinal samples during the patients’ stays, we have sought to describe the immunological changes that occur due to secondary infection as well as after treatment with one of the most used drugs, corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the start of the COVID-19 pandemic, respiratory coinfections have been reported in a large number of studies, and in the first small-scale studies during the initial outbreak in Wuhan (China), coinfections were reported in up to 50% of patients investigated [ 1 ]. There is however substantial variability in the reported prevalence of coinfections with some studies showing rates from 30% to 90% [ [2] , [3] , [4] , [5] ], whereas others report far lower rates [ [6] , [7] , [8] , [9] ]. Studies involving large patient cohorts show a percentage of clinically significant bacterial infections in hospitalized patients of around 4–14%, with the highest incidence being reported in patients on intensive care units (ICU) [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%